The Politics of Power : EU-Russia Energy Relations in the 21st Century - Talseth, Lars-Christian U. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book sheds new light on the complex EU-Russia relationship, by providing a comprehensive account of the EU-Russia Energy dialogue. The author examines why Moscow and Brussels have failed to cooperate in this crucial area of interdependence. By invoking constructivism and Mikhail Bakhtin's concept of dialogue, and drawing on dozens of interviews with Russian and European officials, Talseth argues that the Energy Dialogue was unsuccessful because its interlocutors failed to come up with a common narrative for cooperation. Evidence suggests that the collapse of the Energy Dialogue was not pre-determined and initially there was a great deal of optimism and goodwill. Ultimately, the outcome of the Energy Dialogue was shaped by the unfolding time-space of Russo-European relations. An invaluable reference for students and researchers interested in Russo-European politics, Russo-European energy politics, and energy politics in general. This book will also be of interest to International Relations-scholars focusing on theory and methodology, particularly constructivist research. .
Keywords: Social sciences.; Energy policy.; Energy and state.; Energy security.; Europe -- Politics and government.; European Union.; Russia -- Politics and government.; Environmental policy.; elektronické knihy; electronic books